Positive emotions: exploring the other hemisphere in behavioral medicine. - Chesney MA; Darbes LA; Hoerster K; Taylor JM; Chambers DB; Anderson DE (International Journal of Behavioral Medicine, 2005)
The search for the psychological antecedents of medical disorders has focused on the role of stress and negative emotional states. Previous research in this area has investigated relations between negative emotions and physiological adaptations (e.g., blood pressure elevations), adverse health behaviors (e.g., smoking), and social conditions (e.g., social isolation). In this discussion, we argue that more attention is needed to understand the effects of positive emotional states on health enhancement and disease prevention. In each of the areas cited previously, evidence is beginning to emerge that indicates that positive emotions can be associated with health promoting conditions. Interventions using cognitive behavioral strategies or meditation can increase positive emotional states that are maintained over time and that may benefit health and well-being. Implications for behavioral medicine are discussed.